2016
DOI: 10.1016/j.chemgeo.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Fluid evolution in the Strange Lake granitic pluton, Canada: Implications for HFSE mobilisation

Abstract: 10Strange Lake is a mid-Proterozoic peralkaline granite pluton (Québec-Labrador, Canada) that 11 underwent extreme enrichment in high field strength elements (HFSE), including the rare earth 12 elements (REE). The HFSE mineralisation is confined to highly altered pegmatites and the most 13 altered parts of the granites, implying a genetic association between hydrothermal fluids and 14 HFSE enrichment. This study uses analyses of fluid inclusions to investigate the hydrothermal 15 evolution of the Strange Lake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…Igneous processes such as partial melting, crustal assimilation, melt immiscibility, and fractional crystallization, along with crustal metasomatism, can lead to the formation of REE-enriched carbonatite, alkaline, and peralkaline melts [2,[10][11][12][13][14][15]. Numerous studies have also indicated the importance of hydrothermal processes for the mobilization and concentration of the REE in the late magmatic evolution stages of carbonatite and alkaline/peralkaline systems [4,5,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Igneous processes such as partial melting, crustal assimilation, melt immiscibility, and fractional crystallization, along with crustal metasomatism, can lead to the formation of REE-enriched carbonatite, alkaline, and peralkaline melts [2,[10][11][12][13][14][15]. Numerous studies have also indicated the importance of hydrothermal processes for the mobilization and concentration of the REE in the late magmatic evolution stages of carbonatite and alkaline/peralkaline systems [4,5,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…2). Mineral paragensis and alteration assemblages at Strange Lake have been described by several researchers, including Boily and Williams-Jones (1994), Miller (1986), Salvi and Williams-Jones (1990, 1996, 2006, Gysi and Williams-Jones (2013), Williams-Jones (2014, 2018), and Vasyukova et al (2016).…”
Section: Bedrock Geologymentioning
confidence: 97%
“…This is explained mainly by the abundant incorporation of these metals into the accessory minerals fluorite, monazite, and apatite (Figures 4(a) and 4(b)). The high concentrations in monazite and apatite indicate that the retention was primarily a consequence of the high uptake by phosphates [6], whereas the high concentrations in fluorite also show that this mineral constituted a significant trap at the magmatic stage, in line with observations elsewhere that fluorite can incorporate significant quantities of REE from a melt [57]. Unlike the phosphates, fluorite was also abundant in greisen and veins, with an overall pattern of decreasing REE concentrations in the sequence granite>greisen>veins (Figure 8(a)).…”
Section: Physicochemical Evolution Of the Hydrothermal Systemmentioning
confidence: 99%
“…The growing demand for rare earth elements (REE) in modern techniques for a sustainable environment has been associated with extensive prospecting for these metals worldwide [1]. Numerous laboratory experiments and genetic models have incorporated fluid-inclusion and isotopic data and/or trace element partitioning calculations to understand how REE are transported, fractionated, and ultimately deposited in ores typically associated to the formation or alteration of carbonatitic and alkaline to peralkaline rocks [2][3][4][5][6]. REE enrichment in these systems is often ascribed to magmatic processes that can concentrate REE in fluoride liquids over silicate melt through liquid immiscibility [7] or in primary REE-rich minerals such as phosphates and zircon crystallizing from magma [8].…”
Section: Introductionmentioning
confidence: 99%